ANALISA PENGARUH IKLIM ORGANISASI DAN RASA PERCAYA TERHADAP KOMITMEN KARYAWAN DALAM MENGHADAPI PERUBAHAN STRATEGI PERUSAHAAN (STUDI KASUS PADA PT. SURYAJAYA TEKNOTAMA) - Kusuma, Indra; Purwoko, Bambang; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
In the era of rapid change, the company is required to always be able to face challenges and competitions by making adjustment in strategy. The members of organization's commitment to the strategy chosen by company is very crucial.To support the commitment in company required a good corporate climate and also trust among members of the company. The purpose of this study is to analyze the influence of organizational climate and trust in the commitment of the organization. The study was conducted at PT Suryajaya Teknotama the subjects were employees in that company. The collection of data conducted by interview, studying company documents and using questionnaires. The number of respondents in this study is 202 people. Analysis of the data in this study using SEM and lisrel 8.8 as tools to help analysis the data. Based on the analysis, obtained results showed significant effect of organizational climate to trust, significant effect of trust to commitment. While the organizational climate not significant effect on commitment.